2019
DOI: 10.4186/ej.2019.23.6.419
|View full text |Cite
|
Sign up to set email alerts
|

Applications, Manufacturing and Thermal Characteristics of Micro-Lattice Structures: Current State of the Art

Abstract: Micro-lattice structures are emerging as multi-functional devices. They possess excellent heat transfer capabilities, energy absorption abilities, vibration control abilities, etc. The higher surface area to volume ratio of micro-lattice structures makes them suitable for heat transfer applications where compact and lightweight heat transfer mechanism is necessary such as in case of space and transportation. The heat transfer and mechanical load-bearing properties of micro-lattice structures can be tailored by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The available polymers for MJF are polyamide (PA 11, PA 12) and thermoplastic polyurethane (TPU). MJF is suitable for printing functional mechanical parts or devices, biomedical lattices structures, medical orthotics and prosthetics, mechanical tools, and fluid-tight devices [36,39,[43][44][45][46][47][48].…”
Section: Multi Jet Fusion (Mjf)mentioning
confidence: 99%
“…The available polymers for MJF are polyamide (PA 11, PA 12) and thermoplastic polyurethane (TPU). MJF is suitable for printing functional mechanical parts or devices, biomedical lattices structures, medical orthotics and prosthetics, mechanical tools, and fluid-tight devices [36,39,[43][44][45][46][47][48].…”
Section: Multi Jet Fusion (Mjf)mentioning
confidence: 99%
“…This emerging 3D-printing modality is suitable for low volume production of parts with exceptional mechanical strength, high reusability rate of the powder material, faster production speed as an alternative to injection molding [ 23 , 67 , 103 , 104 ]. MJF is capable of printing functional mechanical parts/devices, biomedical lattices structures, medical orthotics and prosthetics, mechanical tools and fluid-tight devices [ 34 , 67 , 103 , 106 , 108 , 109 , 110 , 111 ]. Figure 4 b shows exemplary high-performance lattice structures 3D-printed by MJF 4200 with cell units ranging from 1.134 to 2.246 mm [ 106 ].…”
Section: Powder-based 3d-printing Modalities and Their Resolutionmentioning
confidence: 99%
“…The powder-based process is one of the most significant and popular class of 3D-printing techniques [ 23 , 24 , 25 , 26 , 27 , 28 ]. This popularity is due to the high reusability rate of the powder material, faster production speed, strong functional parts, lower cost, no or minimum support structures, different fields of application and a large range of compatible materials [ 2 , 3 , 12 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The burgeoning field of 3D printing has changed the way products are manufactured in many industries by offering a higher degree of freedom in design and fabrication with a wide range of materials [ 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have already proven that lattice structures are light in weight, have high impact strength, and have high energy absorption capability [6,7]. The mechanical outcome of various cellular arrangements like an octet, tetrahedral, pyramidal, square, and Kagome were investigated by different researchers during the early progress in research of micro-lattices [8][9][10][11][12][13][14][15][16][17][18]. Recent studies revealed that these different orientation lattice structures have better mechanical properties than honeycombs and other available structures [19].…”
Section: Introductionmentioning
confidence: 99%